2015
DOI: 10.1093/hmg/ddv501
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant disulphide bonding contributes to the ER retention of alpha1-antitrypsin deficiency variants

Abstract: Mutations in alpha1-antitrypsin (AAT) can cause the protein to polymerise and be retained in the endoplasmic reticulum (ER) of hepatocytes. The ensuing systemic AAT deficiency leads to pulmonary emphysema, while intracellular polymers are toxic and cause chronic liver disease. The severity of this process varies considerably between individuals, suggesting the involvement of mechanistic co-factors and potential for therapeutically beneficial interventions. We show in Hepa1.6 cells that the mildly polymerogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 39 publications
3
35
0
Order By: Relevance
“…2A). The patterns of intracellular maturation and secretion for wild-type M and mutant Z AAT variants, measured for comparison, were consistent with those reported previously [24]. Quantification of the three variants using densitometry (n = 2) revealed kinetics of Trento intracellular N-glycan maturation and secretion efficiency only slightly lower than those of wild-type M AAT (Fig.…”
Section: Aat Trento Is Mildly Deficient In Cell Culture Models Of Aatdsupporting
confidence: 89%
See 2 more Smart Citations
“…2A). The patterns of intracellular maturation and secretion for wild-type M and mutant Z AAT variants, measured for comparison, were consistent with those reported previously [24]. Quantification of the three variants using densitometry (n = 2) revealed kinetics of Trento intracellular N-glycan maturation and secretion efficiency only slightly lower than those of wild-type M AAT (Fig.…”
Section: Aat Trento Is Mildly Deficient In Cell Culture Models Of Aatdsupporting
confidence: 89%
“…SERPINA1 alleles are expressed codominantly, and plasma levels of AAT in heterozygous patients are thought to result from the independent contributions of the two variants. However, hetero‐polymerization of the S and Z variants of AAT has been demonstrated by in vitro studies , and an example of heterotypic interactions has been reported in cells between Z and I (R39C) AAT . On this basis, we investigated whether Z AAT coexpression could exacerbate retention of Trento AAT, but this was found not to be the case.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Vectors encoding for the α1AT variants were obtained by site‐directed mutagenesis of M1V (Medicina et al., ) using the QuikChange II Mutagenesis Kit (Agilent) with primers listed in . HEK293T/17 (ATCC#CRL‐11268) or Hepa1‐6 cells (ATCC#CRL‐1830) were maintained in DMEM‐10% FBS (Sigma) and transfected by PEI "Max" (Polysciences Inc.) or Lipofectamine2000 (Thermo Fisher) as previously described (Miranda et al., ; Ronzoni et al., ). Twenty‐four hours after transfection, we collected the cell media and lysed the cells in 1% NP40/20 mM Tris–HCl pH 7.4/150 mM NaCl/10 mM N‐ethylmaleimide/protease inhibitors, then discarding nuclei by 30′ centrifugation at 800 g .…”
Section: Methodsmentioning
confidence: 99%
“…Cysteine mutations and aberrant disulfide bonding underlie the pathogenesis of CD40 deficiency (Lanzi et al, 2010), TNFR1-associated periodic fever syndrome (Lobito et al, 2006) and MiDY insulin-deficient diabetes (Liu et al, 2010). Mutations causing conformational alterations of alpha-1-antitrypsin make its only cysteine more prone to form aberrant disulfide bonds in the ER, thus facilitating the intracellular retention and polymerization of alpha-1-antitrypsin in Alpha-1-antitrypsin deficiency (AATD; Ronzoni et al, 2016). …”
Section: Cysteines and Diseasesmentioning
confidence: 99%